2012
DOI: 10.1111/j.1528-1167.2012.03719.x
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated long‐term forgetting in children with idiopathic generalized epilepsy

Abstract: SUMMARYPurpose: The rapid forgetting of information over long (but not short) delays (accelerated long-term forgetting [ALF]) has been associated with temporal lobe epilepsy but not idiopathic generalized epilepsy (IGE). Long-term memory formation (consolidation) is thought to demand an interaction between medial temporal and neocortical networks, which could be disrupted by epilepsy/seizures themselves. The present study investigates whether ALF is present in children with IGE and whether it relates to epilep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
45
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 38 publications
(55 reference statements)
0
45
0
1
Order By: Relevance
“…Children with epilepsy have an increased risk for memory problems (Menlove and Reilly 2015). When comparing children with epilepsy to typically developing children, studies have shown lowered memory scores on working memory, word lists and stories, irrespective of type of epilepsy (Gascoigne et al 2012;Jambaqué et al 1993;Lopes et al 2014;Northcott et al 2007;Rzezak et al 2017;van Iterson and de Jong 2018). Some conflicting evidence has been found for effects of lateralisation of seizures in focal epilepsy.…”
Section: Introductionmentioning
confidence: 99%
“…Children with epilepsy have an increased risk for memory problems (Menlove and Reilly 2015). When comparing children with epilepsy to typically developing children, studies have shown lowered memory scores on working memory, word lists and stories, irrespective of type of epilepsy (Gascoigne et al 2012;Jambaqué et al 1993;Lopes et al 2014;Northcott et al 2007;Rzezak et al 2017;van Iterson and de Jong 2018). Some conflicting evidence has been found for effects of lateralisation of seizures in focal epilepsy.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in patients who underwent temporal lobectomy, the absence of seizures and being off anti-epileptic drugs was associated with better semantic recall . Finally, seizures themselves may interfere with consolidation (in adults: Blake, Wroe, Breen, & McCarthy, 2000;Mameniskiene, Jatruzis, Kaubrys, & Budrys, 2006;Muhlert et al, 2011; in children: Gascoigne et al, 2012), which in turn could compromise autobiographical memory. Finally, as the hippocampus is purported to be critical for both new learning and recall of past personally experienced episodes, it was expected that the correlations between scores obtained on these two types of memory tests will be high.…”
Section: Introductionmentioning
confidence: 99%
“…It presents as recurrent transient episodes of memory loss; it can be associated with accelerated long-term forgetting (ALF) and autobiographical memory loss. Gascoigne et al (2012) demonstrated that children with idiopathic generalized epilepsy (IGE) may present with ALF, which is related to epilepsy severity. They suggested that their findings might support the notion that the epilepsy or the seizures themselves might disrupt long-term memory consolidation.…”
Section: Transient Epileptic Amnesia and Accelerated Long-term Forgetmentioning
confidence: 99%